Inhibition of TRPC6 Signal Pathway Alleviates Podocyte Injury Induced by TGF-β1 - Haiting Huang; Yanwu You; Xu Lin; Chunrong Tang; Xiangjun Gu; Meiying Huang; Youling Qin; Junhua Tan; Feifan Huang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Transforming growth factor beta 1 (TGF-β1) plays a critical role in the pathogenesis of glomerulosclerosis. The purpose of this study was to examine the effects of inhibition of transient receptor potential cation channel C6 (TRPC6) on podocyte injury induced by TGF-β1 via nephrin and desmin mechanisms. Methods: A rat model of nephropathy was first induced by intravenous injections of adriamycin to determine TRPC6 signal pathway engaged in glomerulosclerosis in vivo. Conditionally immortalized podocytes were cultured in vitro and they were divided into four groups: control; TGF-β1 treatment; TGF-β1 with TRPC6 knockdown and TGF-β1 without TRPC6 knockdown. Real time RT-PCR and Western blot analysis were employed to determine the mRNA and protein of expression of nephrin, desmin and caspase-9, respectively. Flow cytometry was used to examine the apoptotic rate of podocytes and DAPI fluorescent staining was used to determine apoptotic morphology. Results: In vivo experiment, adriamycin significantly upregulated the protein expression of TGF-β1, TRPC6, desmin and caspase-9, and decreased nephrin. Consistent with the latter results, in vitro experiment mRNA and protein expression of desmin and caspase-9 was increased in cultured TGF-β1-treated podocytes, whereas nephrin was declined as compared with the control group. Importantly, TRPC6 knockdown significantly attenuated the upregulated desmin and caspase-9, and alleviated impairment of nephrin induced by TGF-β1. Moreover, typical morphologic features were presented in apoptotic podocytes. The number of apoptotic podocytes was increased after exposure to TGF-β1 and this was alleviated after TRPC6 knockdown. TRPC6 knockdown also decreased an apoptosis rate of TGF-β1-treated podocytes. Note that negative TRPC6 transfection control failed to alter an increase of the apoptosis rate in TGF-β1-treated podocytes. Conclusions: TGF-β1 induced by glomerulosclerosis impairs the protein expression of nephrin and amplifies the protein expression of desmin and caspase -9 via TRPC6 signal pathway. Inhibition of TRPC6 alleviates these changes in podocytes-treated with TGF-β1 and attenuated apoptosis of podocytes. Our data suggest that TRPC6 signal plays an important role in mediating TGF-β1-induced podocyte injury via nephrin, desmin and caspase-9. Results of the current study also indicate that blocking TRPC6 signal pathway has a protective effect on podocyte injury. Targeting one or more of these signaling molecules may present new opportunities for treatment and management of podocyte injury observed in glomerulosclerosis.